Efecto del extracto etanólico de las hojas de Passiflora edulis (maracuyá) sobre la actividad de catalasa en Mus musculus var. swiss. con hiperlipidemia inducida - Angulo Díaz, Diana Carolina (2018)
The objective of the present investigation was to determine the effect of ethanolic extract of leaves of Passiflora edulis on the activity of catalase in hyperlipidemic mice. Thirty mice Mus musculus var. swiss males distributed in five groups. The white group received 10 ml/kg of 0.5% carboxymethylcellulose (CMC) orally (VO) for 7 days, the control group received 10 ml/kg of CMC for VO for 7 days, the problem group I received 50 mg/kg of the ethanolic extract of Passiflora edulis by VO for 7 days, the problem group II, received 300 mg/kg of the ethanolic extract of Passiflora edulis by VO for 7 days, and the standard group received 10 mg/kg by VO for 7 days. On the 6th day, the target group was given 5mL/kg of physiological saline intraperitoneally (VIP), while the other groups involved Triton 400 mg/kg VIP. After 24 hours blood measurements of cholesterol, triglycerides, hemoglobin and catalase activity were performed. The average levels of cholesterol and triglycerides in the control group were consistent with a hyperlipidemia compared to the target group (P<0.05), and significant reductions were also observed in the problem I, problem II and standard groups (P <0.05). The average activity of catalase (U/mL) was: 1412.8 (White), 624.16 (Control), 887.56 (Problem I), 978.46 (Problem II) and 959.50 (Pattern), and the specific activity (U/mg Hb) average was: 9.36 (White), 3.87 (Control), 5.48 (Problem I), 6.03 (Problem II) and 5.94 (Pattern). A significant reduction (P<0.05) in the catalase activity of the control group was found, while a significant increase (P<0.05) was found in the problem II and standard groups; An increase was also observed in problem group I, however it was not significant (P> 0.05). It is concluded that the leaves of Passiflora edulis (passion fruit) at a dose of 300 mg/kg causes a significant increase in catalase activity in experimentally hyperlipidemic animals, demonstrating antioxidant activity